THE IMPORTANCE OF CASE STUDIES IN TEACHING BUSINESS ENGLISH (SCIENCE TIME JOURNAL, 2025)
The use of case studies in teaching Business English has gained significant recognition for its effectiveness in enhancing students' language skills, critical thinking, and real-world problem-solving abilities. This paper explores the role of case studies in Business English instruction, analyzing their advantages, challenges, and implementation strategies. By integrating authentic business scenarios, case studies help learners develop practical language proficiency, negotiation skills, and cultural awareness, which are essential for success in international business environments. The paper concludes with recommendations for educators on how to effectively incorporate case studies into their curriculum.